Analisis Kontribusi Komoditas Tanaman Pangan Palawija Terhadap Inflasi di Kabupaten Aceh Barat - Putri Ansari, Leli; Wahyuningsih, Yayuk Eko; Jalil, Ivon (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to analyze how much secondary food crop commodities (corn, peanuts, cassava and sweet potatoes) contribute to inflation in West Aceh Regency. This research is quantitative research with secondary data sourced from the Central Statistics Agency of West Aceh Regency. This data was collected in a timeseries during 2015-2023. The data analysis model uses contribution calculations to see how big the contribution to inflation is from food crop commodities. Based on the research results, it shows that the agricultural sector of secondary food crop commodities in West Aceh Regency for the type of corn provides the highest contribution to inflation at 28.05 percent. Meanwhile, peanuts provide the highest contribution at 35.02 percent, cassava provides the highest contribution. amounted to 31.29, while sweet potatoes provided the highest contribution at 27.03. Thus, during 2015-2023 the secondary crop food commodity that made the largest contribution to inflation was corn at 13.09 percent, but overall all types of secondary crop food commodities made a low contribution to inflation in West Aceh Regency, namely an average of 10.97 percent is smaller than the average inflation of 25 percent. This shows that the price of palawia food crop commodities in West Aceh Regency is stable.